Dose response effects of the BWF Shuttle Time Programme on children's actual and perceived fundamental movement skill competence. Issue 6 (December 2021) - Duncan, Michael J; Noon, Mark; Clark, Cain CT; Eyre, Emma LJ
This study examined dose-response effects of the Badminton World Federation (BWF) Shuttle Time programme on fundamental movement skills (FMS) and perceived FMS competence in 6–9-year olds. Children (n = 158, 83 boys, 75 girls, Mean ± SD age = 7.6 ± .97) were randomly allocated into three conditions: Shuttle Time 2Xweek; Shuttle Time 1Xweek; 3) control (CON) group. The intervention groups undertook the BWF Shuttle Time programme over a 10-week period in place of both or one of their statutory Physical Education lessons. FMS was assessed from the Test of Gross Motor Development 2. Perceived competence was assessed via the Pictorial Scale of Perceived Movement Skill Competence. Assessments were undertaken pre, post and 10 weeks post intervention. For FMS, a significant time X group interaction (P = .001) was evident. There was no significant difference in FMS between groups at pre (P > .05). Post intervention there were significant differences in FMS between 2X week and 1XWeek (P = .007), 2Xweek and control (P = .0001) and 1X Week and control (P = .007). From post to 10-weeks post there were significant improvements in FMS (P = .001) for the 2X week group. A significant time X group interaction (P = .0001) also indicated that perceived competence increased significantly pre to post for 1Xweek and 2Xweek groups, but not CON groups and was maintained at 10 weeks post (all P = .001).